Monetary policy rules, macroeconomic stability and inflation: a view from the trenches - Athanasios Orphanides (European Central Bank (ECB), 2001)
I estimate a forward-looking monetary policy reaction function for the Federal Reserve for the periods before and after Paul Volcker's appointment as Chairman in 1979, using information that was available to the FOMC in real time from 1966 to 1995. The results suggest broad similarities in policy and point to a forward looking approach to policy consistent with a strong reaction to inflation forecasts during both periods. This contradicts the hypothesis, based on analysis with ex post constructed data, that the instability of the Great Inflation was the result of weak FOMC policy responses to expected inflation. A difference is that prior to Volcker's appointment, policy was too activist in reacting to perceived output gaps that retrospectively proved overambitious. Drawing on contemporaneous accounts of FOMC policy, I discuss the implications of the findings for alternative explanations of the Great Inflation and the improvement in macroeconomic stability since then
Keywords: E3; E52; E58; 330; Greenbook forecasts; monetary policy rules; real-time data; stagflation